Approaches to Culture in Foreign Language Teaching - Sarah MERROUCHE (Revue des Sciences Humaines)
Language and culture are inextricably tied: they cannot be separated without losing their essence and significance. What is language if not a means of communication operating in a defined socio-cultural context? Without language, communication would be very restricted; without culture, there would be no communication at all. A crucial implication is that one cannot be taught without the other.